The Role of Surgical Masks or Respirators to Prevent Coronavirus - Sahaj Sabharwal1, Kaynat Nadeem2 , Muhammad Asif2* (AlQalam Journal of Medical and Applied Sciences, 2020)
The world is suffering from the deadly infection of Coronavirus. The World Health Organization (WHO) has declared the infection as ‘pandemic’. The early symptoms of this deadly infection are high fever, shortness of breath, tiredness and dry cough. So, the entire world is under lockdown to break the chain of COVID-19 with certain precautionary steps is to be ensured. The contemporary ways to sanitize oneself is the 20 seconds formulae of hand wash or using disinfectant containing at least 60% alcohol, avoid touching surfaces and handshakes and no unnecessary contacts. The use of mask and covering face using napkin or elbow while coughing and disposing the napkin would add an added advantage. This review article highlights the role of surgical mask and respirators for controlling this outbreak.